Supervisory control of naturally ventilated buildings - Ljiljana Marjanovic (2002)
In the present climate of energy conservation and CO2 emission consciousness, building heating, ventilating and air conditioning (HVAC) systems are required to achieve thermal comfort and indoor air quality in the most energy efficient manner possible. To this end optimising the use of natural ventilation is considered an area which can significantly reduce both the occupants discomfort and the energy consumption. The ability to effectively control the indoor environment would considerably enhance the use of natural ventilation. The overall aim of this research is to develop, commission and evaluate a fuzzy rule-based controller which can vary the resistance of ventilation opening in order to maintain an acceptable comfort conditions in the occupied space. The design of the fuzzy control system starts by establishing certain quantization levels for the input/output variables along with corresponding membership functions. Aspects of input and output variable choice together with their linguistic labels are explained and presented. Control rules are defined based on the off-line thermal modelling, experimental results and through discussions with experts. A dynamic air flow distribution is investigated through a series of experiments for different environmental conditions and opening levels without any control action. Three rule-bases of different complexity are developed and presented. All solutions are simulated in an input-output space and their differences presented in more detail through examples of the Mamdani inference method application. Controller validation is initially carried out using simulation as this offers the possibility of testing controllers under extreme conditions regardless of test room physical limitations. Simulations are carefully designed to allow simultaneous comparison of different controllers' performances. Then on-line validation is carried out in the test room by measuring the air flow distribution with and without the controller in action. A naturally ventilated test room and its instrumentation is set up. A controller commissioning methodology is established, involving the choice of software and hardware platforms and data acquisition methodology.